Police Efforts in Commanding Drug Criminal Actions in the Muslim Community - Markuat Markuat (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study aims to comprehensively describe the role of the Police in tackling drug crimes in Muslim communities. The research used is juridical empirical. This research is descriptive analysis, namely research that aims to clearly and accurately describe the things in question; then the problems are analyzed based on legal theories or applicable laws and regulations to obtain accountable answers. Based on the results of the study, it was concluded that the role of the Police in tackling drug crimes in Muslim society is the role of preventing, the role of law enforcement and the role in conducting therapy and rehabilitation for narcotics crimes. The efforts made by the Police to tackle drug crimes in Muslim communities are using pre-emptive and preventive methods. Pre-Emtif Effort is a policy that looks at the root causes of crime through a social approach, a situational approach and a community approach to eliminate the elements of potential disturbances. At the same time, preventive efforts are preventing the community so as not to abuse narcotics